2010
DOI: 10.2353/ajpath.2010.100316
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 Overexpression Is Related to the Recurrence of Ovarian Cancer and Confers Resistance to Carboplatin

Abstract: Amplification of the Notch3 locus has been detected in ovarian high-grade serous carcinoma (HGSC), the most common and malignant type of ovarian cancer. We have previously demonstrated that ovarian cancer cells, which amplified and overexpressed Notch3, were dependent on Notch3 signaling for cellular survival and growth. In this study, we provide new evidence that Notch3 expression is associated with recurrent postchemotherapy HGSCs. Moreover, patients with recurrent HGSCs in effusion with high Notch3 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
167
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 29 publications
(31 reference statements)
3
167
0
5
Order By: Relevance
“…Although elevated Notch signaling has been suggested in tumor development, 13,[30][31][32] neither an increase of NOTCH1 expression nor its nuclear translocation was observed in the cases we examined. The cDNA microarray of OSCC showed that neither NOTCH2 nor NOTCH3 was upregulated in OSCC, suggesting that quantitative compensation is unlikely.…”
Section: Discussionmentioning
confidence: 60%
“…Although elevated Notch signaling has been suggested in tumor development, 13,[30][31][32] neither an increase of NOTCH1 expression nor its nuclear translocation was observed in the cases we examined. The cDNA microarray of OSCC showed that neither NOTCH2 nor NOTCH3 was upregulated in OSCC, suggesting that quantitative compensation is unlikely.…”
Section: Discussionmentioning
confidence: 60%
“…Besides hematopoietic malignancy, PBX1 is also highly expressed in solid tumors including melanoma, prostate, ovarian, and breast cancers (23)(24)(25). In ovarian cancer, PBX1 has been identified as an effector in the NOTCH3 signaling pathway, which is known to maintain stemness and promote platinum drug resistance in ovarian cancer cells (10,26). The Notch pathway has also been demonstrated to regulate the PI3K/Akt pathway in stem cells (27) and to regulate ATP-binding cassette protein ABCG2 (28), which can confer multidrug resistance by regulating drug efflux (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of signalling is the combination of Notch ligands with their receptors, which could in turn affect downstream effectors through releasing the intracellular domain of the receptor that is activated by a cascade of proteolytic cleavages mediated by γ‐secretase. For example, it has been reported that NOTCH3 participates in the pathogenesis of EOC recurrence through enhancing carboplatin resistance of cancer cells 15. A high NOTCH4 mRNA expression level was revealed to be significantly correlated with a favourable overall survival (OS) of EOC patients and thus was regarded as a prognostic factor 16.…”
Section: Introductionmentioning
confidence: 99%